2017
DOI: 10.1021/acs.jced.7b00082
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Prediction for the Polarity of Ionic Liquids

Abstract: Ionic liquids (ILs) have attracted remarkable attention as a new class of novel reaction medium and soft functional materials in the framework of Green Chemistry, and the polarity of ionic liquids is one of the primary concerns in the scientific community. Here, we introduce a new and simple scale of polarity, δ μ , for ILs. Initially, two kinds of representative ionic liquids, {1-alkyl-3-methyllimidazolium acetate}) are prepared and confirmed by 1 H NMR spectroscopy and 13 C NMR spectroscopy, respectively. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 89 publications
1
2
0
Order By: Relevance
“…It can be observed that the enthalpy of vaporization obtained from the data of Ravula et al [78] is comparable to the one from the data of Shahbaz et al [77] for ChClG, while it is much larger in the case of ChClU. The computed enthalpies of vaporization from MD are larger than the enthalpies of vaporization found in literature for many ionic liquids [11,17,22,[87][88][89]. The computed SPs are also larger than the ones reported for ILs [8,10,11,13,16,22,88], indicating a more polar nature of the DESs compared to most ILs, when the vaporizing entity is assumed to be a DES cluster.…”
Section: Sps From Vaporization Energysupporting
confidence: 59%
“…It can be observed that the enthalpy of vaporization obtained from the data of Ravula et al [78] is comparable to the one from the data of Shahbaz et al [77] for ChClG, while it is much larger in the case of ChClU. The computed enthalpies of vaporization from MD are larger than the enthalpies of vaporization found in literature for many ionic liquids [11,17,22,[87][88][89]. The computed SPs are also larger than the ones reported for ILs [8,10,11,13,16,22,88], indicating a more polar nature of the DESs compared to most ILs, when the vaporizing entity is assumed to be a DES cluster.…”
Section: Sps From Vaporization Energysupporting
confidence: 59%
“…The relative permittivity of ILs has been obtained from the microwave dielectric spectra, and the values are remarkably lower than those of common polar molecular solvents, which often lead to confusion. , Since the molar electronic transition energy of the longest-wavelength Vis absorption band of betaine dye no. 30 [ E T (30) value] exhibits a good, generally linear correlation with a large number of other solvent-sensitive spectral parameters, such as some UV–vis absorption bands, the hyperfine coupling constant ( A N ), and the Stokes shift of fluorescence spectra in molecular solvents, , and also has the same trend with Z-, Ω-, and S-values as well as many thermodynamic and dynamic data, E T (30) values are widely used as a polarity parameter for ILs. Reichardt et al have collected the E T (30) values of nearly 210 ILs before. Therefore, in this work, E T (30) was chosen as a standard and generally applicable solvent polarity parameter of ILs …”
Section: Introductionmentioning
confidence: 99%
“…Characterization of solvent-solute interactions is a non-trivial task, and many different techniques have been used for this purpose. These include but are not limited to, 1 H and 13 C NMR [14], UV/vis absorption and fluorescence [15][16][17][18][19], octanol-water partition [20], chromatography [20][21][22] and analyzing the solvent effect based on standard chemical reactions [23][24][25][26][27][28]. Physical properties can also provide insight into the macroscopic polar properties of a solvent through for example, refractive index and molar refractivity [29,30], but do not provide detail on intermolecular electrostatic and polarization forces between the solute and solvent.…”
Section: Introductionmentioning
confidence: 99%